Scientific activity of professor Andriy Krasnov and its role in the development of modern geography - Куліш, Сергій Миколайович; Прасул, Юлія Іванівна (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2020)
Purpose. Life, scientific and pedagogical way of А. М. Krasnov at the time of the formation of geography was unique, versatile, often contradictory, but clearly creative and innovative approach to everything that was within his interests. Despite some hasty results that harmed his general authority, the figure of A. M. Krasnov – the professor of Imperial Kharkiv University, the founder of Batumi Botanical Garden – is still of interest. Attention has veen paid to the period of his initial formation as a scientist, communication with V. I. Vernadsky, comparison of A. M. Krasnov’s works with works of other researchers, the implementation of the idea of plant introduction.Method. Authentic scientific works of A. M. Krasnov and his contemporaries have been used in the work. Through the use of historical and historiographical sources and comparative analysis there have been revealed those inconsistencies in his works which caused sharp criticism of reviewers.Results. Studies of the work of the first domestic doctor of geographical sciences Andriy Mykolayovych Krasnov have showed his passion for expeditionary research, charisma, thirst for knowledge, love of nature, rich innovative heritage. Attention has been paid to the initial stage of his life, when the interest in scientific, in particular, expeditionary research, which did not leave him during his life, emerged. Based on the study of the relationship between A. M. Krasnov and V. I. Vernadsky, a conclusion about his extraordinary character, ingrained sense of independence, but also passion, excessive emotionality, haste of conclusions has been made. The authors have given the generalized description of the state of the study of geography, which was considered an auxiliary science in the universities of the Russian Empire in the late XIX century, because for A. M. Krasnov it became a source of innovation. The article reveals the extraordinary scientific courage of A. M. Krasnov, who in his doctoral thesis considered the views of famous scientists on the causes of steppe plains. The analysis of А. М. Krasnov’s publications and other sources has proved that he became the creator of constructive geography, combined theoretical classes with practical ones in nature, initiated student scientific expeditions, founded a student geographical society and a geographical office. Possessing artistic and literary talent, he became one of the best promoters of exotic regions, visiting dozens of countries around the world. The authors have also traced the reasons why his scientific works were treated with skepticism and distrust.Scientific novelty and practical significance. Some details of the relationship between A. M. Krasnov and V. I. Vernadsky have been clarified. The reasons that led to the ignoring of the scientific achievement of A. M. Krasnov by contemporaries have been revealed. It is expedient to use these materials while writing the full scientific and pedagogical biography of professor A. M. Krasnov.